Determination of Epstein?Barr virus (EBV) DNA Load as A Biomarker to Follow up EBV Related Hodgkin’s and Non Hodgkin’s Lymphoma Patients Using Quantitative Competitive Polymerase Chain Reaction Technique (Iraqi Journal of Medical Sciences, 2016)
Background: The Epstein -Barr virus (EBV) is the first human virus implicated in the carcinogenesis. EBV contributes to the carcinogenesis like Hodgkin's Lymphoma (HL) and Non Hodgkin’s Lymphoma (NHL).Objective: Quantitative Competitive Polymerase Chain Reaction (QC-PCR) and ELISA was used to quantitate the EBV DNA load in blood samples of HL and NHL patients pre and post therapy.Methods: EBV DNA extracted from blood samples of 18 HL and NHL patients pre and post therapy, 9 apparently healthy controls used to quantify the EBV DNA load. Quantitative Competitive Polymerase Chain Reaction (QC-PCR) and ELISA were used to quantify EBV DNA load. Wild EBV DNA (WT) obtained by Transformation of Escherichia coli MM 294 with Wild type (WT) DNA plasmid pGEMBamHI-K.Results: EBV DNA load in controls was found to be 7-1.99 × 103 in HL and NHL patients, while in patients it's ranged from zero to 1.936×109 copy numbers per ml of blood. High EBV load with the range of 10715(1.071×104) to 1936421960 (1.936×109) above cut-off value was detected in 66.7% of HL and 5861(5.86×103)-50118(5.01×104) copies/ml blood in 44.5 % of NHL patients pretherapy. After chemotherapy, 60% of HL patients and 100% of HL patients with high EBV load showed significant response. Low viral load was found in 44.45% of patients. Only 55% of lymphoma patients with high EBV load, after chemotherapy 16.6% of them continue to have high EBV DNA load compared to the control group, 38.3% of the patients showed response to chemotherapy when their viral load decreased below cut off value. While 11.1 % continue to have high DNA load. One patient (5.5%) showed an elevated EBV load after completion of chemotherapy.Conclusions: EBV DNA load estimated by Quantitative Competitive Polymerase Chain Reaction considered as valuable promising tumor biomarker in the diagnosis and monitoring of EBV related HL and NHL patients.Key words: Quantitative Competitive Polymerase Chain Reaction (QC-PCR), Epstein-Barr virus (EBV), Viral DNA load, Hodgkin’s (HL) and non Hodgkin’s Lymphoma (NHL) Patients.
Keywords: Quantitative Competitive Polymerase Chain Reaction QCPCR; EpsteinBarr virus EBV; Viral DNA load; Hodgkins HL and non Hodgkins Lymphoma NHL Patients